Psycholinguistic Fundamentals of Non-linearity in Translation - Маргарита Дорофеєва; Анатолій Коцур (Психолінгвістика)
The article is devoted to the psycholinguistic factors of translation non-linearity, realized in the multiple translation solutions. Multiple solutions are caused by the use of translator’s different translation strategies in the same translation situation.